2017
DOI: 10.3892/mmr.2017.8107
|View full text |Cite
|
Sign up to set email alerts
|

Role of DDAH/ADMA pathway in TGF-β1-mediated activation of hepatic stellate cells

Abstract: Asymmetric dimethylarginine (ADMA) is catalyzed by the enzyme dimethylarginine dimethylaminohydrolase (DDAH) in humans, and the role for ADMA has been associated with hepatic fibrogenesis. Transforming growth factor‑β (TGF‑β) has been shown to mediate the myofibroblastic transformation of quiescent hepatic stellate cells (HSCs), a pivotal step in liver fibrogenesis. However, the underlying molecular mechanisms are not well understood. Accumulation of ADMA due to low activity of DDAH has been reported to be ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that hyperglycemia in diabetic patients stimulates HSC activation and proliferation, and contributes to the development of hepatic fibrosis (37,38). EMT is an indispensable mechanism in embryogenesis, development and tissue remodeling, that contributes to the progression of organ fibrosis and cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hyperglycemia in diabetic patients stimulates HSC activation and proliferation, and contributes to the development of hepatic fibrosis (37,38). EMT is an indispensable mechanism in embryogenesis, development and tissue remodeling, that contributes to the progression of organ fibrosis and cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with previous observations in bovine aortic endothelial cells, in which knockdown of DDAH2, in contrast to knockdown of DDAH1, did not affect total DDAH activity 53 . As acknowledged in the introduction section of this manuscript, the results of previous cell culture studies investigating the effect of DDAH2 expression modulation on ADMA metabolism are contradictory; however, an advantage of our studies and the experiments in bovine aortic endothelial cells performed by Pope and colleagues is that we measured DDAH activity in cell lysates using a highly sensitive and reliable stable isotope-based method, whereas most of the prior cell culture studies simply measured ADMA concentrations in culture medium or cell lysates 31 , 54 , 55 . Our results, however, contradict the previous observation that DDAH2 overexpression increased total DDAH activity in microvascular endothelial cells, where DDAH activity was also measured by an isotope-based method 56 .…”
Section: Discussionmentioning
confidence: 95%
“…Abnormal EndMT refers to the process in which endothelial cells gradually lose their original morphology, phenotype and function and obtain the morphology, phenotype and function of mesenchymal cells such as fibroblasts or myofibroblasts. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The expression of VE-cadherin, a specific marker of endothelial cells, is gradually weakened or lost, and the myofibroblast-specific marker α-SMA is expressed instead. 35 Studies have shown that many regulatory factors are involved in the EndMT, of which TGF-β1 is considered to be the most potent factor in the EndMT and myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that increased expression of DDAH inhibits matrix metalloproteinase-9 (MMP9), ADMA, epidermal growth factor receptor (EGFR) and extracellular regulated protein kinases (ERK) signalling pathways, while TGF-β1 inhibits the expression and activity of DDAH, thereby inducing ADMA. 23,24 In addition, studies have shown that TGF-β1 significantly inhibits the expression and activity of nuclear factor erythroid-2-related factor 2 (NRF-2), which is a potential therapeutic target for liver fibrosis. 25 Curcumin (Cur) is a polyphenolic substance that is naturally extracted from the rhizome of turmeric plants and has antifibrotic, anti-inflammatory, antioxidant and hypolipidaemic effects.…”
mentioning
confidence: 99%